¡Mira al cielo! - Alonso, José Ramón 1962- (Editorial Juventud, S. A., 2017)
How many stars are in the universe? Who invented the first telescope? How many moons does Saturn have? Discover the answers to these and many more questions about the Solar System in this informative book
Illustrations on endpapers
Keywords: Raumfahrt; Weltraumforschung; Weltraum; Astronomy / Juvenile literature; Planets / Juvenile literature; Outer space / Exploration / Juvenile literature; Astronomía / Literatura juvenil; Planetas / Literatura juvenil; Espacio exterior / Literatura juvenil; Astronomy; Exploration of outer space; Planets; Outer space; Juvenile works; Kindersachbuch